HUBUNGAN MOTIVASI DAN KOMPETENSI TERHADAP PRODUKTIVITAS KERJA MELALUI KEPUASAN KERJA PEGAWAI: (Studi Pada Perangkat Daerah Pemerintah Kota Mojokerto) - Savia Melati (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2023)
The relationship of motivation and competence to work productivity through employee job satisfaction (study on the regional apparatus of the Mojokerto City Government). Competition in employment is increasing along with technological advances that continue to develop from generation to generation. This phenomenon is triggered by existing globalization and modernization. Organizations strive to find a workforce that has the ability to work effectively and efficiently, with the aim of achieving the goals that have been set. The Mayor of Mojokerto also asked all regional apparatuses to focus on the SAKIP (Device Performance Accountability System) component which is still low in value and emphasized the importance of understanding the Head of Regional Apparatus in carrying out the duties and functions that are the authority in their respective work units to support improving SAKIP achievements. In 2023, there are two out of nine Key Performance Indicators (IKU) of Mojokerto City that are predicted to have not been able to achieve the specified performance targets. These indicators include the Bureaucratic Reform Index and the Economic Growth Rate. Therefore, greater and specific efforts are needed to be able to produce targeted solutions in the future. It is necessary to further strive for performance improvement through motivation, competence and job satisfaction that affect the level of work productivity.